Albania : Sixth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility Request for a Waiver of Nonobservance of Performance Criterion and Financing Assurances Review. (IMF Staff Country Reports; Country Report ;, 2005)
This paper discusses key findings of the Sixth Review Under the Extended Arrangement Under the Poverty Reduction and Growth Facility (PRGF) for Albania. The macroeconomic performance of the Albanian economy has been good overall, with sustained growth and low inflation. Weak infrastructure and institutions, however, hold back export performance, and the economy remains dependent on migrant remittances to finance a large trade deficit. The 2005 macroeconomic outlook remains at 6 percent growth and about 3 percent inflation.